Use of managament acounting systems in the hotel and restaurant business - Yembergenov, R.A. (BUKETOV BUSINESS REVIEW, 2019)
In conditions of high uncertainty, as in the hotel-restaurant industry, it is imperative that managers make extensive use of information, including the management accounting system to make decisions. An appropriate management accounting system can satisfy the information needs of hotel and restaurant managers, since management accounting systems are an integral part of business information and control systems aimed at supporting management decision-making. In practice, managers must use a wide range of information, from both internal and external sources, and convert raw data into useful information when making decisions, because enterprises are under pressure both inside and outside sources. In this article the author explores the use of enterprise management systems. The satisfaction of managers with the details and availability of information is assessed by the management accounting system. A comprehensive performance assessment requires a balanced focus on both financial and non-financial indicators. Performance evaluations based solely on financial measures may have an undesirable effect on the behavior of managers. The results show that General managers and middle managers equally use the management accounting system for shortterm and long-term decisions. However, a detailed analysis of group managers data requires additional research.